Impulsiveness moderates the effects of exogenous attention on the sensitivity to gains and losses in risky lotteries - Alejandro Hirmas; Jan Engelmann (Tinbergen Institute, 2022)
Does attention have a causal impact on risky decisions? We address this question in a preregistered experiment in which participants accept or reject a series of mixed gambles while exogenously varying how information can be sampled. Specifically, in each trial participants observe the outcomes of a mixed-gamble with gains and losses presented sequentially. To isolate the causal role of attention on the decision process, we manipulate for how long each outcome is presented before showing the next one. Our results partially confirm our preregistered hypotheses that longer exposure to an outcome increases its weight on the decision. We find specific effects in the domain of losses, but not gains. A longer presentation duration of losses leads to increased sensitivity for losses, such that lotteries with higher losses are rejected more often when losses are presented for longer. To our surprise, when gains are presented for longer, the participants show increased sensitivity to both gain and loss values in their decision. Further analyses show that specifically participants with higher impulsiveness become more sensitive to outcome values when gains are presented for longer. Attentional impulsiveness is the strongest driver of this effect. Jointly, these results support the notion that attention has a causal impact on risky choice. Moreover, our results underline the moderating role of impulsiveness on the relationship between attention and choice.
Keywords: D91; D81; D83; D87; 330; Attention; Impulsiveness; Loss Aversion; Random Utility Models